Pengaruh Alat Bantu Media Terhadap Keterampilan Hasil Lay Up Shoot Pada Ekstrakurikuler Bola Basket SMA Negeri 1 Sukatani: Media anti-media Tool, basketball lay up shoot skills. - Thalia Eka Putri; Febi Kurniawan; Habibi Hadi Wijaya (Universitas Singaperbangsa, 2021)
The purpose of making this thesis is to answer the formulation of research problem, namely is there the effect of media aids on the skills of lay-up shoots in basketball extracurricular activities at Sma Negeri 1 Sukatani. The author uses a quantitative approach with experimental methods and uses a one group pretest-posttest design. The sampling technique uses saturated samples. The instrument used was a test of the result of the lay-up shoot in basketball game. There are theree stages in this research, namely, pretest, treatment and posttest. Treatment was carried out in eight meetings. From the pretest and posttest result there is an average inrease of 1.94%. the pretest normality test was normally distributed LO<Ltable, namely 0.148<0.154. the posttest normality test was normality distributed LO<Ltabel, namely 0.146<0.154. homogeneity test of the homogeneous variant Fcount <Ftable is 1.11<1.82. the difference test for the two mean tcount -5.24>2.042 Ho is rejected, which means that there is a difference betwen the pretest and poesttest, so that there aids on the skills of the shoot lay-up results on basketball exstracurriculer activities at Sma Negeri 1 Sukatani.